Linearly polarised planar inverted f-antenna for global positioning system and worldwide interoperability for microwave access applications - Agarwal M.; Singh R.; Meshram M.K. (My University, 2025)
A compact dual-band planar inverted-F antenna in conjunction with an inverted L-shaped parasitic and reduced ground-plane structure working in the GPS (Global Positioning System) band(1565-1585 MHz) and Worldwide Interoperability for Microwave Access band (3300-3800 MHz) is presented. The antenna meets the strict space requirements of the portable devices and the finaldesign fits a volume of 100 × 24 × 9.7 mm3 (L ×W× H). It is composed of a series of branches, properly dimensioned and separated to generate the resonances at the desired frequencies. The antenna is fabricated using a 0.2 mm thick copper foil. The linearly polarised antenna exhibits good impedance matching performance, wide beam radiation pattern andhigh gain. Also, carrier-to-noise ratios for three different satellite locations, that is, 5°,50° and 90° elevation are 47.58, 50.49 and 45.86 dB/Hz, respectively, at the centre frequency (1575 MHz) of GPS L1 band, which is well within the maximum allowable limit (50.5 dB/Hz) at room temperature. © The Institution of Engineering and Technology 2013.